OMALIZUMAB: EXPANDED OPPORTUNITIES FOR THE ATOPIC DISEASES TREATMENT - T.V. Kulichenko (Union of pediatricians of Russia, 2009)
The review highlights experience and administration perspectives of the immunobiological medication Omalizumab in allergy. Omalizumab is the anti'IgE monoclonal antibody. Growing successful experience of anti'IgE application confirms the assumption that treatment by Omalizumab may modify the course of bronchial asthma, by preventing the remodeling processes in the respiratory tracts and reducing hyperactivity of bronchi. Today, it is widely discussed what other possible areas of anti'IgE therapy there might be. Omalizumab might be very important in treatment of different potentially IgE'dependent diseases, among which there is urticaria and angioneurotic edema, allergic rhinitis, nasal polyposis and severe forms of allergic conjunctivitis. Besides, Omalizumab, as part of the allergen specific immunotherapy protocol, may also provide sizable advantages. The author reveals potential role of Omalizumab in treatment of other atopic diseases, such as allergic bronchopulmonary aspergillosis, atopic dermatitis and food allergy.Key words: Omalizumab, anti'IgE therapy, biological agents, IgЕ, bronchial asthma, allergic rhinitis, atopic dermatitis, idiopathic urticaria fever, treatment, children.